(untitled) (Journal of Oriental Studies, 2023)
The problem of the Islamization of Moghulistan as a medieval state in the eastern part of Central Asia which was included in the uluses of Chagatai and Kaidu, remains insufficiently researched in historiography. In the 14th-16th centuries, significant events took place related to the Islamization of the Turkic-Mongolian people of this state headed by the Chagatai Khans. The policy of the khans Togluk-Timur, Khizr-Khoja, Mohammed, Yunus Khan, and other rulers of Moghulistan toward actively support Islam was due to the objective needs of the social integration of subject tribes and regions, and the strengthening of supreme power. At the same time, it cannot be ruled out that the khans became sincere admirers of the charismatic spiritual teachers of Tasawwuf (Sufism). Based on information from medieval writings and a comparative analysis of the scientific works of predecessors, the article presents a holistic picture of the Islamization of Moghulistan: the prerequisites, the course of Islamization in the context of the biographies of khans and hagiographies of Sufi sheikhs, aspects of Islamization of nomadic tribes (on the example of the Kirghiz), the significance of Islam in the polity`s history. The problem is studied on the basis of modern theoretical and methodological approaches, as a paradigm of traditional Islam of the Hanafi madhhab (with more liberal criteria in religious attribution of communities), the author’s thesis about the completion of the Islamization of the Kazakhs and Kyrgyz in the 15th-16th centuries, the idea of a creative historical role of outstanding personalities of khans and Hoja (Sufis) in medieval Central Asian states, also taking into account the thesis about the commonality of the spiritual and civilizational history of the region.